Mediating Islamic Ecotheology in the Digital Age: A Framing Analysis of Hablum Minal Alam and Ecological Hijrah - Sarifatul Insaniyah; Abdullah Hosseinieskandian (Journal of Digital Religion and Contemporary Society, 2026)
This article examines the representation of ecological hijrah and the concept of Hablum Minal Alam (the human-nature relationship) in Greenpeace Indonesia’s YouTube podcast, as featured on the @lyfewithless account. Amidst the environmental crisis and the digitalization of religiosity, this study examines how Islamic ecological theology is mediated and negotiated in the digital space. Using Robert N. Entman’s framing analysis, the study finds that overconsumption and exploitation of nature are framed as moral issues that demand lifestyle changes and individual ecological awareness. This narrative emphasizes practical ethics but has yet to penetrate the spiritual dimension of the ecological crisis. The findings reveal that ecological hijrah is portrayed as a form of digital piety that integrates faith and sustainability, yet it remains vulnerable to being commodified by the logic of social media. This article contributes to the development of Islamic digital ecology studies by revealing the ambiguity between authenticity and performativity in online ecological activism and providing a reflective framework for integrating spirituality and sustainability in the digital space.